Challenges of Front-End Engineering (FEE) in Construction Industry in Malaysia - Yik Jiunn, Ng; Noor Yasmin Binti Zainun, (Recent Trends in Civil Engineering and Built Environment, 2021)
Front-End Engineering (FEE) is an early stage of a construction process that helps to identify risks in capital project planning phases. It is also known as Front-End Planning (FEP), Front-End Engineering Design (FEED), Front-End Loading (FEL) and pre-project planning. This paper is conducted to identify the challenges of FEE in construction industry in Malaysia and propose solutions for the challenges. The preliminary data of the challenges of FEE were gathered from literature review. Questionnaire was made to collect data for analysis. Questionnaire consists of 3 sections which are demographic profile, general perspective of respondents and challenges of FEE. There are 11 challenges of FEE were proposed in questionnaire. Questionnaire was reviewed by the experts before distributing to the respondents. Questionnaire was distributed to construction parties such as developers, contractors, consultants and suppliers in Kuala Lumpur, Malaysia. Collected data were analysed by using Statistical Package for the Social Sciences (SPSS) software version 28. Principal Component Analysis (PCA) was used to analyse the critical challenges of FEE. From the PCA results, critical challenges of FEE obtained are (1) leadership quality, (2) skilled labour shortage, (3) communication barrier, (4) lack of supports from top management and (5) lack of expertise or professionals. Therefore, it can be concluded that the most critical challenges of FEE were on the human factors.